COMPARISON OF SERUM SODIUM, SERUM POTASSIUM, AND BLOOD HEMOGLOBIN CHANGES AFTER TRANSURETHRAL RESECTION OF THE PROSTATE BETWEEN IRRIGATION WITH NORMAL SALINE AND STERILE WATER - Kurniawan, Wikan; Utomo, Trisula (Indonesian Journal of Urology, 2011)
Objective: This study aims to know whether there are significant differences of blood sodium, potassium and hemoglobin level among patients post TURP who was irrigated by using normal saline and the sterile water. Material & Method: This is a single blind randomized clinical trial study performed from September 1, 2008 until August 31, 2009. Thirty-one subjects participated in this study. The subjects were divided into two groups, 14 subjects for normal saline (group I) irrigation and 17 subjects for sterilized water irrigation (group II). Results: There are statistically differences (p < 0,05) between hemoglobin concentrations changes in group I, and hemoglobin and sodium concentration changes in group II. There were no statistically differences (p > 0,05) in sodium and potassium changes in group I and potassium in group II. There are no statistically differences in hemoglobin, sodium, and potassium changes among two groups. Conclusion: Normal saline irrigant for irrigation after TURP give more stable post operative electrolyte profile compared to sterilized water. Keywords: TUR prostate, irrigation, serum sodium, potassium level differences.